Adat Ipilah: A Traumatic Life Experience - Lanawati Lanawati; Theresia Ivana (Universitas Muhammadiyah Semarang, 2020)
Adat Ipilah is a mandatory customary sanction given to women who are pregnant out of wedlock by the Dayak Ma'anyan tribe in Central Kalimantan, Indonesia as a form of sanction for social violations. Carried out on pregnant women in the first trimester, generally in the first pregnancy. Pregnant women will demonstrate in front of traditional and community elders. The implementation of Ipilah can be a stressor and affect the psychological health of pregnant women. The research was to explore the impact of the implementation of the Ipilah custom on the psychology of Dayak Ma'anyan women. Using qualitative methods with an interpretive phenomenology approach. Participants were selected using a purposive sampling technique. Data collection by in-depth interviews. Analyzed using interpretative phenomenological analysis. Get 6 themes; Disappointed with adat, forced to follow Ipilah, afraid of the sanctions that will be received, ashamed to interact with the community, pressured because cannot forget Ipilah, helpless with the situation. Ipilah sanction was a traumatic experience that had a negative psychological impact. Ipilah is a source of stressors that affect the lives of women who experience it. Whether it's psychological or social relations in society.